2021
DOI: 10.1172/jci.insight.141462
|View full text |Cite
|
Sign up to set email alerts
|

Failure of thymic deletion and instability of autoreactive Tregs drive autoimmunity in immune-privileged liver

Abstract: The liver is an immune-privileged organ that can deactivate autoreactive T cells. Yet in autoimmune hepatitis (AIH), autoreactive T cells can defy hepatic control and attack the liver. To elucidate how tolerance to self-antigens is lost during AIH pathogenesis, we generated a spontaneous mouse model of AIH, based on recognition of an MHC class II–restricted model peptide in hepatocytes by autoreactive CD4 + T cells. We found that the hepatic peptide was not expressed in the thymus, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Although MHC I expression is low, hepatocytes can prime CD8 T cells, which mostly results in CD8 T cell death [ 35 , 36 ] or profound unresponsiveness even in infection [ 37 ]. MHC II expression is low or absent in steady-state [ 38 ], but can be upregulated in inflammatory conditions, rendering hepatocytes functional antigen-presenting cells that promote tolerance rather than inflammation [ 39 , 40 ]. Besides direct antigen presentation by hepatocytes, it is conceivable that hepatocytes can also deliver antigen to neighbouring professional antigen-presenting cells, e.g.…”
Section: Liver Tolerancementioning
confidence: 99%
“…Although MHC I expression is low, hepatocytes can prime CD8 T cells, which mostly results in CD8 T cell death [ 35 , 36 ] or profound unresponsiveness even in infection [ 37 ]. MHC II expression is low or absent in steady-state [ 38 ], but can be upregulated in inflammatory conditions, rendering hepatocytes functional antigen-presenting cells that promote tolerance rather than inflammation [ 39 , 40 ]. Besides direct antigen presentation by hepatocytes, it is conceivable that hepatocytes can also deliver antigen to neighbouring professional antigen-presenting cells, e.g.…”
Section: Liver Tolerancementioning
confidence: 99%
“…Recently, Preti et al. investigated the role of autoreactive CD4 T cells in an LCMV-related AIH model ( 27 ). They constructed a transgenic mouse in which the CLIP sequence of the CD74 has been replaced by the immunodominant CD4 epitope GP 61-80 specifically in the liver.…”
Section: Traditional Modelsmentioning
confidence: 99%
“…Interestingly, they found that besides an activation of liver-infiltrating CD4 T cells, the mice also displayed a reduced functionality of GP-specific regulatory T cells. In combination a chronic form of AIH-like disease, with interface hepatitis, formation of autoantibodies, as well as elevated IgG and ALT levels ensued ( 27 ). Although, this model uses modified autoantigen-presentation and autoantigen-specific TcR, these data indicate that the tolerogenic environment in the liver might be overcome via autoreactive CD4, rather than CD8, T cells.…”
Section: Traditional Modelsmentioning
confidence: 99%
“…In a mouse model of AIH, characterized by hepatocellular expression of a MHC-class II restricted immunodominant epitope of the lymphocyte choriomeningitis virus and by accumulation of CD4 T-cells specifically recognizing this epitope, Preti et al. proposed that liver damage was fostered by selective failure of peripherally induced autoreactive Tregs ( 81 ). Notably these autoreactive Tregs not only were reduced in frequency but also displayed heightened IL-17 production and reduced epigenetic demethylation ( 81 ), postulating a role for altered epigenetic regulation in Treg impairment in this model.…”
Section: Treg Impairment In Aih: the Role Of Cd39mentioning
confidence: 99%
“…In a mouse model of AIH, characterized by hepatocellular expression of a MHC-class II restricted immunodominant epitope of the lymphocyte choriomeningitis virus and by accumulation of CD4 T-cells specifically recognizing this epitope, Preti et al proposed that liver damage was fostered by selective failure of peripherally induced autoreactive Tregs (81). Notably these autoreactive Tregs not only were reduced in frequency but also displayed heightened IL-17 production and reduced epigenetic demethylation (81), postulating a role for altered epigenetic regulation in Treg impairment in this model. In human AIH, FOXP3 demethylation -a typical feature of bona fide Tregs -was retained in some studies (75,79) and altered in others, where AIH derived Tregs were highly methylated (82); this indicates that further studies are needed to clearly establish the role of FOXP3 epigenetic regulation in AIH Tregs.…”
Section: Treg Impairment In Aih: the Role Of Cd39mentioning
confidence: 99%